Predicting Employment Status of Injured Workers Following a Case Management Intervention - Awang, Halimah; Mansor, Norma (Elsevier, 2018)
Background: The success of an injury intervention program can be measured by the proportion of successful return to work (RTW). This study examined factors of successful return to employment among workers suffering from work-related injuries. Methods: Data were obtained from the Social Security Organization, Malaysia database consisting of 10,049 RTW program participants in 2010–2014. The dependent variable was the RTW outcome which consisted of RTW with same employer, RTW with new employer or unsuccessful return. Multinomial logistic regression was performed to test the likelihood of successful return with same employer and new employer against unsuccessful return. Results: Overall, 65.3% of injured workers were successfully returned to employment, 52.8% to the same employer and 12.5% to new employer. Employer interest; motivation; age 30–49 years; intervention less than 9 months; occupational disease; injuries in the lower limbs, upper limbs, and general injuries; and working in the manufacturing, services, and electrical/electronics were associated with returning to work with the same employer against unsuccessful return. Male, employer interest, motivation, age 49 years or younger, intervention less than 6 months, occupational disease, injuries in the upper limbs and services sector of employment were associated with returning to new employer against unsuccessful return. Conclusion: There is a need to strengthen employer commitment for early and intensified intervention that will lead to improvement in the RTW outcome.